Digital Public Complaint Portals and Human Rights-Based Investigative Oversight: Strengthening Police Accountability at the East Nusa Tenggara Regional Police - Annas Abdullah Tetapo (Manunggal Halim Jaya, 2026)
Digital transformation has emerged as an essential mechanism for enhancing transparency, accountability, and public participation within the Indonesian National Police (Polri). As a law enforcement institution with investigative authority, Polri requires effective oversight mechanisms to ensure that investigative processes comply with legal standards and human rights principles. This study aims to examine the role of the Dumas Presisi application in supporting human rights-based investigative oversight and strengthening legal accountability within the Internal Supervision Division (Itwasda) of the East Nusa Tenggara Regional Police. This study employs a normative legal research method using statutory and conceptual approaches. Legal materials were obtained from relevant regulations, academic literature, and previous studies concerning police accountability, procedural justice, public participation, and digital governance. The findings reveal that Dumas Presisi functions not merely as a digital complaint platform but also as an oversight mechanism that facilitates investigation evaluation, prevents potential abuse of authority, improves institutional performance, and strengthens public participation in police supervision. This study demonstrates that digital complaint mechanisms can contribute to the development of a police oversight model that integrates legal accountability, community participation, and human rights protection. The effectiveness of this model depends on transparent complaint management, systematic follow-up procedures, and the utilization of public feedback as a basis for continuous institutional improvement.